GURU PENGGERAK - Roslaeni (Jurnal Pendidikan Agama Islam, 2024)
Motivating Teacher Education is Leadership program for to become learning leaders. This program includes online training, workshops, conferences, and 6 months mentoring for aspiring teacher movers. During the program, the mover teacher continues to carry out his teaching duties as a teacher. The goals of independent learning with Motivating Teacher Education are expected to: 1) have a "growth mindset", so that they are able to carry out various effective learning innovations for students, 2) can create "psychological safety" in the learning process so that students can grow the habit of asking questions, lots of trials, and lots of work without having to worry about failure.This program aims to boost teacher potential and increase student independence in learning. The driving teacher is part of the educational reform process for the better, and has a fundamental role in the implementation of independent learning.